NILAI CINTA KASIH DALAM NOVEL NO PLACE LIKE HOME KARYA ALMA ARIDATHA DAN IMPLEMENTASINYA DALAM PEMBELAJARAN TEKS NOVEL KELAS XII SMA - Utami, Indri Yasa; Asri, Yasnur (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this research is to describe and analyze intrinsic elements, the value of love, and the implementation of the value of love in Alma Aridatha's No Place Like Home novel in novel text learning in class XII high school students. This type of research is qualitative research with descriptive methods. The data source in this research is the No Place Like Home novel by Alma Aridatha. The results of the research were found as participants. First, there are seven intrinsic elements in Alma Aridatha's No Place Like Home novel, namely themes, characterizations, background, plot, point of view, language style, and mandate. Second, there are four values of love in Alma Aridatha's No Place Like Home novel, namely (1) 12 data the values of love for God; (2) 37 data the values of love for the family; (3) 12 data the values of love for others; and (4) 11 data the values of love for oneself. Third, the implementation of the value of love in Alma Aridatha's No Place Like Home novel in novel text learning class XII high school students 2013 curriculum with basic competencies related to three aspects of assessment, namely the assessment of knowledge, attitudes, and skills. Based on the results of the research, it is expected that the teacher suggests the No Place Like Home novel by Alma Aridatha which is easily understood by students in novel text learning in high school so that learning objectives are achieved.Â Kata Kunci: nilai cinta kasih, pembelajaran teks novel